MURĀBAḤAH SEBAGAI INSTRUMEN PEMBIAYAAN DALAM KEUANGAN ISLAM MODERN - Maulidizen, Ahmad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2017)
Islamic banking in Indonesia has experienced significant growth, including assets, financing provided and the number of customers. Islamic bank financing 70-80% is given to the community by using the contract of murābahah, in the form of consumptive and productive. Islamic bank operations must be guided by Fatwa of the National Sharia Council in order to carry out its optimal function economically and to run the Shari'a comprehensively. Therefore, this article will explain about the concept of murābahah conceptually and application in Islamic Bank in Indonesia. The purpose of writing this article so that the implementation of Murābahah contract in Islamic Bank in Indonesia can be in accordance with the principles of Shari'a that put forward the principle of justice and no party is harmed